2008
DOI: 10.1080/01635580701684849
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Fruit and Vegetable Consumption and Genetic Variation on NAD(P)H:Quinone Oxidoreductase (NQO1) Phenotype in an Endoscopy-Based Population

Abstract: NAD(P)H:quinone oxidoreductase (NQO1) is an inducible detoxification enzyme relevant for colorectal cancer biochemoprevention. We evaluated the influence of recent fruit and vegetable (F&V) consumption and polymorphisms in NQO1 and transcription factor NFE2L2 on rectal NQO1 phenotype and also whether white blood cell (WBC) NQO1 activity reflects rectal activity. Among 94 sigmoidoscopy patients, we assessed F&V consumption by dietary record and determined the NQO1 c.609C > T and g.-718A > G and NFE2L2 g.-650C >… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…After retrieving the full text of these 29 articles, we excluded 9 articles because of the following reasons: one reported the association between the NQO1 609C>T SNP and H. pylori seropositivity [54]; one did not focus on the NQO1 609C>T but on NQO1 R139W SNP (rs4986998) [55]; three were for the association between the NQO1 609C>T SNP and colorectal adenoma [56], [57], [58]; two were for the correlation between the NQO1 609C>T genotypes and NQO1 activity [59] or telomere length [60]; two were for review or meta-analysis articles [61], [62]. In addition, the Caucasian control group (252 Caucasian controls) in the study by Zhang et al [45] had overlapped subjects used in the study by Sarbia et al [43], and the esophageal cancer patients (193 cases) in the study by Zhang et al [63] were also overlapped with those in the same author's study [45].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After retrieving the full text of these 29 articles, we excluded 9 articles because of the following reasons: one reported the association between the NQO1 609C>T SNP and H. pylori seropositivity [54]; one did not focus on the NQO1 609C>T but on NQO1 R139W SNP (rs4986998) [55]; three were for the association between the NQO1 609C>T SNP and colorectal adenoma [56], [57], [58]; two were for the correlation between the NQO1 609C>T genotypes and NQO1 activity [59] or telomere length [60]; two were for review or meta-analysis articles [61], [62]. In addition, the Caucasian control group (252 Caucasian controls) in the study by Zhang et al [45] had overlapped subjects used in the study by Sarbia et al [43], and the esophageal cancer patients (193 cases) in the study by Zhang et al [63] were also overlapped with those in the same author's study [45].…”
Section: Resultsmentioning
confidence: 99%
“…Main characteristics of the included publications are presented in Table 1 . Among the 20 publications, four studies were for esophageal cancer [45], [64], [65], [66], one for gastric cancer [67], nine for colorectal cancer [55], [59], [68], [69], [70], [71], [72], [73], [74], [75], [76], two for pancreatic cancer [77], [78], one for liver cancer [79], and three for multiple types of GI cancers [43], [63], [80]. Of all studies, 11 studies were conducted in Caucasian populations [43], [65], [66], [68], [71], [72], [73], [74], [75], [76], [77], [78], seven in Asian populations [63], [64], [67], [69], [70], [79], [80], and two in multiple populations [45], [76].…”
Section: Resultsmentioning
confidence: 99%
“…It might be that the carried T genotype of NQO1 produced a mutant enzyme affects the activity but does not affect mRNA and plasma protein expression (Chen et al, 2004 ). However, Tijhuis et al demonstrated that the NQO1 609C/T polymorphism has a great effect on rectal NQO1 mRNA level and enzyme activity (Tijhuis et al, 2008 ). It might be that NQO1 609C/T polymorphism in different diseases has different functions, which need more experimental results to be confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…Single‐nucleotide polymorphisms (SNPs) are the most frequent type of variation and powerful tools for medical genetic studies (Wang et al, 1998 ). The NQO1 gene genetic variations or polymorphisms that produce a functionally altered enzyme may also affect the risk of different diseases, including METH dependence (Hubackova et al, 2009 ; Ohgake et al, 2005 ; Tijhuis et al, 2008 ). To date, associations between NQO1 SNPs and multiple kinds of diseases have been widely studied, especially the rs1800566 (609C/T), a cytosine (C) to thymine (T) change at nucleotide position 609 in exon 6 which resulted in a proline‐to‐serine amino acid change at codon 187 of the amino acid sequence of the protein.…”
Section: Introductionmentioning
confidence: 99%
“…Of these, three articles that did not explore NQO1 rs1800566 genetic polymorphisms were excluded. During the extraction of data, two articles [23,24] were excluded because of unavailable data, one article was excluded for it was not a case-control study [25], another one [26] was excluded because the studied population was overlapped with another study [27], and another one article was retrieved in both PubMed and Elsevier ScienceDirect. Thus, 12 studies were included in the current meta-analysis [27][28][29][30][31][32][33][34][35][36][37][38].…”
Section: Study Characteristicsmentioning
confidence: 99%